Climate change and plant genomic plasticity - Carlo M. Pozzi; Angelo Gaiti; Alberto Spada (Theoretical and Applied Genetics, 2025)
Key message Genome adaptation, driven by mutations, transposable elements, and structural variations, relies on plasticity and instability. This allows populations to evolve, enhance fitness, and adapt to challenges like climate change. Abstract Genomes adapt via mutations, transposable elements, DNA structural changes, and epigenetics. Genome plasticity enhances fitness by providing the genetic variation necessary for organisms to adapt their traits and survive, which is especially critical during rapid climate shifts. This plasticity often stems from genome instability, which facilitates significant genomic alterations like duplications or deletions. While potentially harmful initially, these changes increase genetic diversity, aiding adaptation. Major genome reorganizations arise from polyploidization and horizontal gene transfer, both linked to instability. Plasticity and restructuring can modify Quantitative Trait Loci (QTLs), contributing to adaptation. Tools like landscape genomics identify climate-selected regions, resurrection ecology reveals past adaptive responses, and pangenome analysis examines a species’ complete gene set. Signatures of past selection include reduced diversity and allele frequency shifts. Gene expression plasticity allows environmental adaptation without genetic change through mechanisms like alternative splicing, tailoring protein function. Co-opted transposable elements also generate genetic and regulatory diversity, contributing to genome evolution. This review consolidates these findings, repositioning genome instability not as a mere source of random error but as a fundamental evolutionary engine that provides the rapid adaptive potential required for plant survival in the face of accelerating climate change.